The role of training in improving the entrepreneurship competency of sustainable rehabilitation participants BNN West Java - Sumadhinata, Yelli Eka; Ramadhan, Nabilah; Riantani, Suskim (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
To strengthen the economy, the government is pushing empowerment initiatives for new businesses. However, for fellow participants in continuous rehabilitation for BNN West Java Province customers, business activities might be a chance to start a new life and be accepted by society. This research examines the impact of entrepreneurship training on BNN West Java Province customers' sustained recovery. This research employed descriptive data analysis to evaluate the training and entrepreneurship skills of sustainable rehabilitation participants for BNN foster clients in West Java Province. According to SPSS study, entrepreneurship training increases entrepreneurial skills by 65.9%. The results of this study are expected to motivate the government, private sector, and other organizations to organize better entrepreneurship training to help fellow participants in sustainable rehabilitation by preparing them to become part of the community again through entrepreneurial activities.